The prognosis of bladder cancer is affected by fatty acid metabolism, inflammation, and hypoxia - Xiao, Yu; Yang, Junfeng; Yang, Maolin; Len, Jinjun; Yu, Yanhong (Frontiers in Oncology, 2022)
Background：The prognosis of bladder cancer (BC) is poor, and there is no effective personalized management method for BC patients at present. Developing an accurate model is helpful to make treatment plan and prognosis analysis for BC patients. Endogenous fatty acid metabolism causes cancer cells to become hypoxic, and the coexistence of hypoxia and inflammation is often characteristic of cancer. All three together influence the tumor immune microenvironment, treatment and prognosis of BC. Methods: We used TCGA-BLAC cohorts as a train group to build a risk model based on fatty acid metabolism, hypoxia and inflammation-related gene signatures and performed external validation with GSE13507, GSE31684 and GSE39281 cohorts. We validated the model to correlate with the clinicopathological characteristics of patients, created an accuracy nomogram, and explored the differences in immune microenvironment and enrichment pathways between high and low risk groups of patients. And we investigated the correlation of risk scores with coproptosis, pyroptosis, m7G and immune checkpoint-related genes. Results: We found significant differences in overall survival and progression-free survival between high- and low-risk groups, and patients in the low-risk group had a better prognosis than those in the high-risk group. In the train group, the AUCs for predicting overall survival at 1, 3, and 5 years were 0.745, 0.712, and 0.729, respectively. The 1-, 3-, and 5-year overall survival AUCs were 0.589, 0.672, and 0.666 in the external validation group, respectively. The risk score independently predicted the prognosis of BC patients with an AUC of 0.729. And there was a significant correlation between risk scores and BC clinicopathological features, and in the GSE13507 cohort, we observed that BC progression and deeper invasion were associated with higher risk scores. Risk scores were highly correlated with, coproptosis, pyroptosis, m7G, immune checkpoint-related genes and immune microenvironment. In addition, we found that patients in the low-risk group responded better to immunotherapy, whereas patients in the high-risk group were more sensitive to commonly used chemotherapy drugs. Conclusion: Our findings provide new treatment decisions for BC, and can effectively predict the prognosis of BC patients, which is helpful for the management of BC patients.